2020
DOI: 10.1186/s13058-020-01308-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of crown-like structures in breast adipose tissue and clinical outcomes among African-American and White women with breast cancer

Abstract: Background: Crown-like structures in breast adipose tissue (CLS-B), composed of necrotic adipocytes encircled by macrophages, are associated with obesity and hypothesized to worsen breast cancer prognosis; however, data are sparse, particularly in multi-racial populations. Methods:We assessed specimens for CLS-B from 174 African-American and 168 White women with stage I-III breast cancer treated by mastectomy. Benign breast tissue from an uninvolved quadrant was immunohistochemically stained for CD68 to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
2
33
1
Order By: Relevance
“…At the tissue level, several studies have demonstrated that CLS-B are positively correlated with breast adipocyte diameter, as would be expected given their association with obesity [ 67 , 69 , 70 , 71 , 73 , 81 , 83 , 84 ]. Even among ideal-weight women, a positive, linear association was found between CLS-B density and adipocyte diameter (ρ = 0.36; p < 0.01) [ 71 ].…”
Section: Potential Etiologic Drivers Of Cls-bmentioning
confidence: 78%
See 4 more Smart Citations
“…At the tissue level, several studies have demonstrated that CLS-B are positively correlated with breast adipocyte diameter, as would be expected given their association with obesity [ 67 , 69 , 70 , 71 , 73 , 81 , 83 , 84 ]. Even among ideal-weight women, a positive, linear association was found between CLS-B density and adipocyte diameter (ρ = 0.36; p < 0.01) [ 71 ].…”
Section: Potential Etiologic Drivers Of Cls-bmentioning
confidence: 78%
“…No minimum amount of encirclement has been proposed for defining CLS-B. One study used ≥50% encirclement for primary analyses and made comparisons using higher cut points (≥75% and ≥90%) with few differences in conclusions by cut point used [ 69 ]. Based on the study’s definition of CLS-B, a breast pathologist then enumerates CLS-B typically by visual assessment.…”
Section: Crown-like Structures Of the Breast (Cls-b): Histologic Marker Of Local Inflammationmentioning
confidence: 99%
See 3 more Smart Citations